Numerical and experimental analyses of the chemical heterogeneity of a solidifying heavy ductile-cast-iron roller - Stransky, Karel (Materiali in tehnologije, 2012)
The quality of the working rollers used for rolling rails is determined by the chemical and structural compositions of the material of the rollers and the production technology. It is necessary to cast rollers with significantly improved utility properties, i.e., mainly a high wear resistance and optimal mechanical and structural properties. It is, therefore, necessary to find and ensure the optimal relationships between the matrix structure and the resulting values of the mechanical properties of the rollers in order to maximize their life time. The requirements introduced here cannot be ensured without a knowledge of the kinetics of the solidification. Therefore, numerical and experimental investigations of the temperature field of the solidifying roller were conducted. The kinetics of the solidification has a measurable and non-negligible influence on the chemical and structural heterogeneity of the investigated type of ductile cast-iron. Linking to the results of the model of the temperature field of the cast rollers, an original methodology was developed for the measurement of chemical micro-heterogeneity. The structure of this cast-iron is created by a large amount of the transition form of graphite and a small amount of globular graphite, and also the lamellar graphite and cementite, whereas the structure of the metal matrix is perlitic. The volume amounts of the structural components were determined using a quantitative metallographic analysis, according to which the places for the analysis of the element composition using X-ray energy-dispersive spectral micro-analysis were selected. The chemical and structural heterogeneity of the cast roller is, therefore, a significant function of the method of melting, modification and inoculation and the successive procedures of risering, casting and crystallization after cooling.
Keywords: siva litina s kroglastim grafitom; spheroidal graphite cast iron; roller; valj; strjevanje; solidification; chemical and structural heterogeneity; kemijska in strukturna heterogenost; methodology for measurement; metodologija meritev